1986
DOI: 10.1111/j.1528-1157.1986.tb05741.x
|View full text |Cite
|
Sign up to set email alerts
|

Interictal Behavioral Features of Patients With Epilepsy

Abstract: Three questions are dealt with in this paper. (1) Do patients with epilepsy differ behaviorally from normal control groups and from persons with other medical and neurological conditions with respect to emotional adjustment, and if so, in what ways? (2) Are patients with temporal lobe epilepsy different emotionally or behaviorally from patients with other types of epilepsy? (3) To what degree does underlying brain dysfunction create a substrate for abnormal and maladaptive behavior? A review of the literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 47 publications
1
38
0
1
Order By: Relevance
“…The presence of active epilepsy (i.e., persistence of seizures in the preceding 6 months) was another risk factor for depression and a hallmark of the severity of psychiatric symptoms. An association was found by others between depression and increased seizure frequency (26,27). By contrast, fewer psychosocial problems were reported by patients who were seizure free and off drugs in the preceding year in a community-based sample (28).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The presence of active epilepsy (i.e., persistence of seizures in the preceding 6 months) was another risk factor for depression and a hallmark of the severity of psychiatric symptoms. An association was found by others between depression and increased seizure frequency (26,27). By contrast, fewer psychosocial problems were reported by patients who were seizure free and off drugs in the preceding year in a community-based sample (28).…”
Section: Discussionmentioning
confidence: 97%
“…Depression is defined by a score of ≥8. Severity of depression also can be categorized as follows: mild (8)(9)(10)(11)(12), moderate (13)(14)(15)(16)(17), major (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and severe (30-52) (9). HRQOL was measured by using the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) (10), a form developed for the assessment of the general health and functional capability.…”
Section: Tests For the Diagnosis Of Depression And For The Assessmentmentioning
confidence: 99%
“…Furthermore, Kanner and Palac (2000) have emphasized the clinical significance of this epilepsy-specific mood disorder, demonstrating that at least three quarters of epilepsy patients with depressive symptoms have non-clinical depression according to the Diagnostic and Statistical Manual of Mental Disorders Fourth Edition (DSM-IV) criteria, and that anhedonia without sadness or irritability may predominate. However, others refute the idea of an epilepsy-specific mood disorder and suggest that depressive symptoms in epilepsy are similar to those seen in patients without epilepsy ( Standage and Fenton 1975;Dodrill and Batzel 1986;Metcalfe et al 1988;Reilly et al 2006). Overall, the prevailing idea is that the constellation of depressive symptoms in patients with epilepsy mostly overlaps with that observed among patients with idiopathic major depression (Lambert and Robertson 1999).…”
Section: Introductionmentioning
confidence: 90%
“…Also seizures, especially secondarily generalized seizures, might have an effect on cognition. In patients with a high number of secondarily generalized tonic-clonic seizures (SGTCS), cognitive decline has been described (Dodrill, 2002;Dodrill and Batzel, 1986;Stefan and Pauli, 2002; Thompson and Duncan, 2005;Trimble, 1988), although data are sometimes contradictory (Helmstaedter and Elger, 1999;Kramer et al, 2006). In various preclinical and clinical studies, changes in cerebral metabolism (Bernasconi et al, 2002;Jokeit et al, 1997;Miller et al, 2000;Tasch et al, 1999) and neuronal loss (Kotloski et al, 2002) were observed shortly after SGTCS.…”
Section: Introductionmentioning
confidence: 99%